The Effect Of Radiation On Radiology Technologists: A Comprehensive Review (Journal of Namibian Studies : History Politics Culture, 2022)
Radiology technologists are indispensable members of the healthcare team, playing a crucial role in diagnostic imaging procedures that aid in the detection and management of various medical conditions. This comprehensive review explores the impact of radiation exposure on these healthcare professionals, examining sources, mechanisms of cellular damage, and associated health risks. It delves into the potential for radiation-induced DNA damage, cell cycle disruption, inflammation, and immune suppression. Potential health consequences, including cancer, cardiovascular diseases, reproductive issues, cataract formation, skin disorders, and neurological effects, are discussed. Essential radiation protection measures are highlighted, encompassing time, distance, shielding, personal protective equipment, dosimetry monitoring, facility design, safety training, regulatory compliance, and dose optimization. By understanding radiation's effects and implementing effective protective strategies, radiology technologists can continue providing vital diagnostic services while safeguarding their long-term well-being.